2021
DOI: 10.1080/23802359.2020.1861567
|View full text |Cite
|
Sign up to set email alerts
|

The complete chloroplast genome of Onosma fuyunensis Y. He & Q.R. Liu and its phylogenetic analysis

Abstract: The chloroplast genome sequences of Chinese Boraginaceae species, Onosma fuyunensis Y. He & Q.R. Liu, were reported in this study. We sequenced O. fuyunensis using the Illumina HiSeq X Ten platform. The total length of O. fuyunensis chloroplast genome is 150,612 bp, including a large single-copy region of length 82,853 bp, a small single-copy region of length 17,281 bp, and a pair of 25,239-bp inverted repeat regions. The chloroplast genome of O. fuyunensis has 133 genes, including 84 protein-coding, eight rib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 10 publications
1
3
0
3
Order By: Relevance
“…The analysis demonstrated that the M. sikkimensis chloroplast genome spanned a length of 149,428 bp, and it featured the circular quadripartite typical of chloroplast genomes, consisting of the LSC, SSC, and a pair of IR regions. Gene annotation indicated that the genome contains 112 genes, which include 78 protein-coding genes, 30 tRNA genes, and 4 rRNA genes, which is consistent with the genomic structure and gene quantity observed in the chloroplasts of other species within the Boraginaceae family [47][48][49][50][51]. Introns were crucial for the regulatory mechanisms that control gene expression.…”
Section: Discussionsupporting
confidence: 68%
“…The analysis demonstrated that the M. sikkimensis chloroplast genome spanned a length of 149,428 bp, and it featured the circular quadripartite typical of chloroplast genomes, consisting of the LSC, SSC, and a pair of IR regions. Gene annotation indicated that the genome contains 112 genes, which include 78 protein-coding genes, 30 tRNA genes, and 4 rRNA genes, which is consistent with the genomic structure and gene quantity observed in the chloroplasts of other species within the Boraginaceae family [47][48][49][50][51]. Introns were crucial for the regulatory mechanisms that control gene expression.…”
Section: Discussionsupporting
confidence: 68%
“… 2022 ), Onosma fuyunensis NC_049569 (He et al. 2021 ), Trigonotis peduncularis MZ911745 (Wu et al. 2022 ), Agastache rugosa MW760849 (Wang et al.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding clinical studies, 2 small-sample cohort studies by He et al showed that bisoprolol 40 and metoprolol 41 increased lumbar spine BMD and reduced the fracture incidence among elderly Chinese men with hypertension who did not take calcium supplements. Khosla et al 42 conducted a randomized controlled trial in 155 postmenopausal American women, excluding those who had taken bisphosphonates.…”
Section: Sbbsmentioning
confidence: 99%